CONTESTING DOMINATION: MODERNITY, COLONIALITY OF GENDER, AND DECOLONIAL FEMINISM IN JOSÉ DE LA CUADRA'S "LA TIGRA". - RAMOS, JUAN G. (Romance Notes, 2015)
The article focuses on the literature of Ecuador, as reflected in" La Tigra", one of the significant works on author José de la Cuadra. Topics discussed include social issues of the era like global economic crisis, the assassination of erstwhile president José Eloy Alfaro Delgado, and the beginning of democracy, De la Cuadra's affinity towards realism in his short stories and reflection on feminism, modernity, and colonialism.